Adoption of Use-Oriented Product-Service Systems for Electronic Devices in Austria: Exploring Key Acceptance Factors - Astner Emma; Falkenberg Christof; Pöchtrager Siegfried (Die Bodenkultur)
E-waste has one of the greatest impacts on the environment and is the fastest-growing waste stream globally. The ever-ongoing growth in our economy and unsustainable consumption patterns ask for a change. Use-oriented product-service systems (u-PSS) are a promising business model to address this change by acting toward a circular economy. However, the implementation of u-PSS can face various challenges because it requires a fundamental shift in how companies interact with consumers as well as consumers’ preferences. Therefore, this study aims to identify factors of acceptance for adopting u-PSS for electronic devices in Austria. To gather specific data, an online survey was conducted with 287 participants. The hypotheses were tested using multiple regression analysis. The results reveal that out of the tested factors, environmental awareness and information are the most important factors of acceptance. For a successful implementation, key determinants include service provision, device durability, and comprehensive information about u-PSS.